2013
DOI: 10.1177/0961203313511555
|View full text |Cite
|
Sign up to set email alerts
|

Extended follow-up of the CYCLOFA-LUNE trial comparing two sequential induction and maintenance treatment regimens for proliferative lupus nephritis based either on cyclophosphamide or on cyclosporine A

Abstract: Objective To evaluate the extended follow-up of the CYCLOFA-LUNE trial, a randomized prospective trial comparing two sequential induction and maintenance treatment regimens for proliferative lupus nephritis based either on cyclophosphamide (CPH) or cyclosporine A (CyA). Patients and methods Data for kidney function and adverse events were collected by a cross-sectional survey for 38 of 40 patients initially randomized in the CYCLOFA-LUNE trial. Results The median follow-up time was 7.7 years (range 5.0-10.3). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 15 publications
(15 reference statements)
0
12
0
1
Order By: Relevance
“…Multiple small RCTs showed that lupus nephritis induction with calcineurin inhibitors (cyclosporine or tacrolimus) is as effective as cyclophosphamide or mycophenolate [200203]. A recent metanalysis suggested a possible superiority of tacrolimus over cyclophosphamide [204].…”
Section: Managementmentioning
confidence: 99%
“…Multiple small RCTs showed that lupus nephritis induction with calcineurin inhibitors (cyclosporine or tacrolimus) is as effective as cyclophosphamide or mycophenolate [200203]. A recent metanalysis suggested a possible superiority of tacrolimus over cyclophosphamide [204].…”
Section: Managementmentioning
confidence: 99%
“…Most evidence suggests CyA efficacy in proliferative lupus nephritis, as supported by few case series [66,[73][74][75][76][77][78] and uncontrolled trials [79,80]. In addition, CyA has been shown to be more beneficial than steroids alone [81] and as effective as AZA [82] and cyclophosphamide (CTX), both at short [83] and long term follow-up [84]. As a whole, it can be stated that CyA treatment in proliferative lupus nephritis displays a cumulative rate of complete or partial remission approaching 90%, with an important antiproteinuric effect [85].…”
Section: Cyclosporine a In Systemic Lupus Erythematosusmentioning
confidence: 99%
“…Cyclosporin A (CYS A) is an immunosuppressant agent widely used in the context of antirejection therapy. In rheumatology, the drug is approved for the treatment of rheumatoid (RA) and psoriatic arthritis (PA), but in clinical practice, it is also daily employed to treat other connective tissue diseases (CTDs) such as systemic lupus erythematosus (SLE), dermatomyositis (DM), and in patients suffering from systemic vasculitis …”
Section: Introductionmentioning
confidence: 99%